Positron Emission Tomography Techniques to Measure Active Inflammation, Fibrosis and Angiogenesis: Potential for Non-invasive Imaging of Hypertensive Heart Failure - Balogh, Viktoria; MacAskill, Mark G.; Hadoke, Patrick W. F.; Gray, Gillian A.; Tavares, Adriana A. S. (Frontiers in Cardiovascular Medicine, 2021)
Heart failure, which is responsible for a high number of deaths worldwide, can develop due to chronic hypertension. Heart failure can involve and progress through several different pathways, including: fibrosis, inflammation, and angiogenesis. Early and specific detection of changes in the myocardium during the transition to heart failure can be made via the use of molecular imaging techniques, including positron emission tomography (PET). Traditional cardiovascular PET techniques, such as myocardial perfusion imaging and sympathetic innervation imaging, have been established at the clinical level but are often lacking in pathway and target specificity that is important for assessment of heart failure. Therefore, there is a need to identify new PET imaging markers of inflammation, fibrosis and angiogenesis that could aid diagnosis, staging and treatment of hypertensive heart failure. This review will provide an overview of key mechanisms underlying hypertensive heart failure and will present the latest developments in PET probes for detection of cardiovascular inflammation, fibrosis and angiogenesis. Currently, selective PET probes for detection of angiogenesis remain elusive but promising PET probes for specific targeting of inflammation and fibrosis are rapidly progressing into clinical use.